Dairy cattle reproduction is a tightly regulated genetic process: Highlights on genes, pathways, and biological processes. (1st January 2015) - Valour, D.; Michot, P.; Eozenou, C.; Lefebvre, R.; Bonnet, A.; Capitan, A.; Uzbekova, S.; Sellem, E.; Ponsart, C.; Schibler, L.
Abstract: Herd fertility is a key factor for the sustainability of cattle farming. However, declining fertility has become one of the main causes of culling and replacement of cows in developed countries. Omics technologies have been successfully developed in cattle, refining our knowledge of molecular mechanisms governing cattle reproduction. However, most studies have failed to establish clear links between the genome and final phenotypes. Further studies will be needed to integrate all Omics data and develop a systems biology modeling approach to tackle this complex biological function.